2004
DOI: 10.1074/jbc.c400118200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for the Immunophilin FKBP52 in Copper Transport

Abstract: FK506-binding protein 52 (FKBP52) is an immunophilin that possesses peptidylprolyl cis/trans-isomerase(PPIase) activity and is a component of a subclass of steroid hormone receptor complexes. Several recent studies indicate that immunophilins can regulate neuronal survival and nerve regeneration although the molecular mechanisms are poorly understood. To investigate the function of FKBP52 in the nervous system, we employed a yeast two-hybrid strategy using the PPIase domain (domain I) as bait to screen a neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…For example, FKBP52 binds to Atox1, a metallochaperone that plays a role in delivering copper for export by the Wilson and Menkes proteins, and overexpression of FKBP52 enhances copper release in a cell culture model system (49). There are other proteins that are involved in metal homeostasis and that have polyhistidine regions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FKBP52 binds to Atox1, a metallochaperone that plays a role in delivering copper for export by the Wilson and Menkes proteins, and overexpression of FKBP52 enhances copper release in a cell culture model system (49). There are other proteins that are involved in metal homeostasis and that have polyhistidine regions.…”
Section: Discussionmentioning
confidence: 99%
“…None of the other known members of the FKBP family has a metal-binding domain similar to the C-terminal sequence of SlyD, but several have been implicated in metal homeostasis pathways. For example, a recent study demonstrated that FKBP52 interacts with the copper metallochaperone Atox1 and has a role in copper efflux (42). Mouse FKBP23 contains two Ca(II)-binding EF-hand motifs, and the ER-localized protein may act as a Ca(II)-dependent chaperone (43).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the process of copper transfer by Atox1 is further facilitated by some other proteins or by protein modifications. Recent yeast two-hybrid and immunoprecipitation studies demonstrated interaction between immunophilin FKBP52 and Atox1 that was enhanced in a copper-supplemented medium (82). Furthermore, over-expression of FKBP52 in HEK293 cells increased copper efflux similarly to over-expression of ATP7B.…”
Section: Atox1-mediated Copper Transfermentioning
confidence: 99%